ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN INTEGRITAS TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN MEDIASI KOMITMEN ORGANISASI (Studi pada Perawat RSUD Ar Rozy Kota Probolinggo) - Kencana, Listya Nanda; Muryati, Muryati; Mas, Nasharuddin (Bajang Institute, 2024)
The aim of this research is to obtain empirical evidence of the ability of leadership style and integrity to encourage increased OCB, both directly and through the mediation of organizational commitment. Type of research is quantitative with the SEM-SmartPLS method. Data was obtained through questionnaires distributed to 55 nurses at Ar Rozy Regional Hospital, Probolinggo City. The sample is determined by census or saturated sample. Empirical evidence shows that both leadership style and integrity are able to encourage increased OCB and organizational commitment. It's just that the role of organizational commitment is weak in mediating the influence of leadership style on OCB. However, organizational commitment is able to play a strong role in mediating the influence of integrity on nurses' OCB at Ar Rozy Regional Hospital, Probolinggo City.